2012
DOI: 10.1155/2012/406852
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Prevalence and Mortality of Dementia in Elderly Hong Kong Population: Projections, Disease Burden, and Implications for Long-Term Care

Abstract: Background. We describe the trends in prevalence and mortality of dementia among older people in Hong Kong over time. Projections of the number of older people with dementia through 2039 and estimation of the disease burden are also included. Methods. Prevalence data were extracted from previous studies in Hong Kong. Mortality data were obtained from the Department of Health of Hong Kong. Projections of the number of people with dementia were calculated by applying the prevalence rates of dementia obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 20 publications
0
58
0
Order By: Relevance
“…1 In Hong Kong, the estimated number of persons with dementia was 103 433 among those aged 60 years or above in 2009, and this number is projected to increase to 332 688 by 2039. 2 Dementia is a clinical syndrome due to a variety of causes. The most common is Alzheimer's disease (AD) followed by vascular dementia.…”
Section: Challenges In the Diagnosis And Management Of Dementia In Homentioning
confidence: 99%
“…1 In Hong Kong, the estimated number of persons with dementia was 103 433 among those aged 60 years or above in 2009, and this number is projected to increase to 332 688 by 2039. 2 Dementia is a clinical syndrome due to a variety of causes. The most common is Alzheimer's disease (AD) followed by vascular dementia.…”
Section: Challenges In the Diagnosis And Management Of Dementia In Homentioning
confidence: 99%
“…The number of community-dwelling elderly individuals aged ≥70 years suffering from dementia will increase from approximately 70,000 at present to 222,400 by 2036 [7,8,9]. With the ageing population, Hong Kong is expected to experience increasingly larger numbers of older people with dementia in the future [10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Compared to the population without dementia, the authors reported that these LE were shorter by 7 years for both sexes. Similarly, another study [11] reported that there were 286,313 disability-adjusted life years (DALY) lost due to dementia for people aged ≥60 years in 2006. Female elderly individuals tend to carry two third of the total DALY burden.…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, the range of prevalence in the previous 8 studies since 1980 was from 2.7% to 4.4% [6]. In Hong Kong, the prevalence in the people aged 70 and over was estimated to increase from 4.5% to 9.3% since 1995 [7]. A recent review which included 48 studies in mainland China, Hong Kong and Taiwan from 1980 to 2010 provided a pooled estimate for the population aged 60 and over as 3.0% (95% CI: 2.4-3.9), ranging from 0.6-9.0% across age-bands, and reported higher prevalence in northern China (3.9%, 95% CI: 2.8-5.5) than in southern China (2.9%, 95% CI: 1.9-3.6) [5].…”
Section: Introductionmentioning
confidence: 99%